Modeling, simulation and experimental investigation of closed loop MPPT based single phase stand alone photo voltaic system using particle swarm optimization technique - V. Thakre, P; M. Deshmukh, V (International Journal of Engineering and Technology, 2018)
Standalone photovoltaic (PV) systems are implemented to perform independently from the utility grid. Such system are beneficial for certain AC as well as DC loads; that too especially where conventional energy cannot reach. To make such system more efficient and independent, a closed loop control could be employed. This research paper presents a novel approach to model and simulate a closed loop maximum peak power tracking (MPPT) based single phase stand alone system using particle swarm optimization (PSO) technique. Based on the simulation results, an experimental investigation has been successfully carried out.Â